Pemilihan sistem perparitan sementara untuk diaplikasi di tapak bina - Mahazir, Mashanim (2006)
A researched have been conducted to identify method of temporary drainage system that existed at construction site, to identify factors that influenced the selection of temporary drainage to be applied at construction site thus used to develop structured framework system towards the selection of appropriate temporary drainage system to be applied at construction site. Grass lined Channel, Temporary Earthern Diversion Dike, Asphalt Pavement Swales, Geotexile Swales and Earth Swales were the temporary drainage systems that existed in order to minimize or to overcome the problem occurred. Percentage obtained trough qualitative data analysis from participated consultants, contractors and analysis made from case studies of construction site were gained to identify prior factors that influenced the selection of temporary drainage. Through the factors identified, a structured framework system was developed and can be used as guidance to consultants in designing the appropriate temporary drainage system to be applied by the contractor at construction site. Regular maintenance, appropriate design by the consultant, endorsement obtained from the relevant authority, adequate budget allocation in constructing the system, the application of computer aided in selecting the suitable system to be applied, will make the application at the construction site more effective for current use and future.